Geographical information system on logistics management for industrialized building system - Mohd Aizat, Mohd Hanif (2012)
Now the construction industry is facing challenges from several aspects, there are cost, quality and safety. Through the implementation of industrialized building system all challenges can be faced with ease. However, an effective management of supply for industrialized building system is crucial. The need for an accurate and timely information system is essential for providing information logistics management of industrialized building system. Logistic management process can be done quickly if the information can be obtained quickly. Geographical Information System (GIS) can be use to assist in providing information for logistics management. GIS is a computer based system designed to support geographical information storage, analysis, manipulation and spatial data presentation. This project discusses the potential of GIS in order to provide effective information that can assist in logistics management. For this purpose, the modeling step has been made. GIS model can be generated through the relevant data on industrial building system that needed for logistics management. The processing, analysis, presentation and inquiry of spatial data are performed using ArcGIS software so that a database and result of analysis can be stored and displayed in a digital form. With this application, the information required will be shown on the computer screen and this can be acquired easily and quickly.